Near-infrared rhodol dyes bearing salicylaldehyde moieties for ratiometric pH sensing in live cells during mitophagy and under hypoxia conditions. Issue 13 (20th February 2023) - Dwivedi, Sushil K.; Arachchige, Dilka Liyana; Vohs, Tara; Tang, Jiani; Usimaki, Kyle; Olowolagba, Adenike Mary; Fritz, Delaney Raine; Luck, Rudy L; Werner, Thomas; Liu, Haiying
Abstract : We describe a simple but efficient approach to make fluorescent probes A and B based on rhodol dyes incorporated with salicyaldehyde moiety for monitoring pH changes in mitochondria under oxidative stresses and hypoxia conditions, and for tracking mitophagy processes. Abstract : We describe a simple but efficient approach to make fluorescent probes A and B based on rhodol dyes incorporated with salicyaldehyde moiety for monitoring pH changes in mitochondria under oxidative stresses and hypoxia conditions, and for tracking mitophagy processes. Probes A and B possess p K a values (p K a ≈ 6.41 and 6.83 respectively) near physiological pH and exhibit decent mitochondria-targeted capabilities, low cytotoxicity, and useful ratiometric and reversible pH responses, which make the probes appropriate for monitoring pH fluctuations of mitochondria in living cells with built-in calibration feature for quantitative analysis. The probes have been effectively useful for the ratiometric determination of pH variations of mitochondria under the stimuli of carbonyl cyanide-4(trifluoromethoxy)phenylhydrazone (FCCP), hydrogen peroxide (H2 O2 ), and N-acetyl cysteine (NAC), and during mitophagy triggered by cell nutrient deprivation, and under hypoxia conditions with cobalt chloride (CoCl2 ) treatment in living cells. In addition, probe A was efficient in visualizing pH changes in the larvae of fruit flies.